Coffee pulp: An industrial by-product with uses in agriculture, nutrition and biotechnology - Carmen M.-T. (2020)
The coffee shell or pulp is the first by-product obtained from the processing of coffee. It represents approximately 40 to 50% of the coffee berry’s weight. Currently, in much of the industry, it is a waste product with a major environmental impact on the water and soil, flora and fauna, and a problem to nearby populations in terms of odor and proliferation of insects and pathogenic microorganisms. This is a review that compiles alternative uses of coffee pulp in agriculture, food and nutrition, medicine and biotechnology. In food and agriculture, for example, the pulp can be used as organic fertilizer to improve degraded soils, in the biological control of plant pathogens, as food or substrate for microorganisms and worms, as feed for chickens, sheep, goats, fish and other animals, and in the productions of foods and beverages for human consumption. In biotechnology, coffee pulp can be used in the cultivation of edible fungi, production of enzymes, substrate for caffeine degrading microorganisms and for microorganisms that produce natural fungicides. Although many of these applications have been proposed and studied, there are also several novel uses that are in the early stages of development; for example, the use of pulp bioactive compounds to make food supplements, or to increase dietary fiber contents in foods and beverages, as well as for the production of biocontainers and biopackaging, alternatives to plastics and their serious environmental impact. © 2020 Reviews in Agricultural Science.